Spontaneous confession at the civil matter site (Revista de Investigaciones Universidad del Quindío, 2021)
In civil matters, proof must be considered as an action to demonstrate a right or fact according to the established means, it is to demonstrate the truth or falsehood, which is equated to the existence or nonexistence of something. In this sense, the spontaneous confession at the site, deductively addresses a description of the legal precept within the doctrinal and normative framework that exists in this regard through a theoretical methodological process that details the elements of location, evidence and confession.
Keywords: confession; trial; evidence